Effect of Fermented Local Feed on Egg Quality of Laying Quail - Agasi, Satri Yusasra; Maulana, Fajri (Jurnal Biologi Tropis, 2025)
Improving feed efficiency through local resources is essential for sustainable quail production. This study aimed to evaluate the effect of fermented local feed on the egg quality of laying quail. A randomized block design (RBD) was used, consisting of four treatments with four replications: RA (100% commercial feed/control), RB (90% commercial + 10% fermented local feed), RC (80% + 20%), and RD (70% + 30%). Data were analyzed using ANOVA followed by Duncan’s multiple range test. The results showed that the substitution of commercial feed with fermented local feed had no significant effect (P>0.05) on yolk index, albumen index, and eggshell thickness, but significantly improved yolk color (P<0.01). At weeks 7–8, values were: yolk index 0.504 ± 0.014, yolk color 5.65 ± 0.66, albumen index 0.071 ± 0.010, and eggshell thickness 0.209 ± 0.014. At weeks 12–13, values were: yolk index 0.488 ± 0.208, yolk color 5.70 ± 0.48, albumen index 0.075 ± 0.006, and eggshell thickness 0.205 ± 0.010. It is concluded that up to 30% of commercial feed can be replaced with fermented local feed without compromising egg quality. This finding supports the utilization of local feed resources in quail farming and offers a cost-effective alternative to commercial diets.